Antifungal potential of extracts of the microalgae Pyramimonas virginica against dermatophyte fungi (Research, Society and Development, 2024)
The aim of this study was to evaluate the antifungal potential of the extracts centrifuged and electroflocculated of the microalgae Pyramimonas virginica against dermatophyte fungi. To obtain the microalgal biomass, the culture was carried out in a 10 L tubular photobioreactor, in triplicates. The harvesting of microalgal biomass was performed by two methods, centrifugation and electroflocculation. For the extraction of microalgal biomass, the absolute ethanol (99.9%) solvent was used. The antifungal activity of the extracts was evaluated by broth microdilution method, in the concentration range of 0.0115 to 6 mg mL-1. The Minimum Inhibitory Concentration (MIC) was determined visually, by the absence of fungal growth. Extracts were tested against the dermatophytes Nannizzia gypsea, Trichophyton mentagrophytes and Trichophyton tonsurans. Both centrifuged and electroflocculated extracts were able to inhibit the growth of all dermatophytes evaluated, and the centrifuged extract was more active than the electroflocculated. The extracts showed lower MIC values against T. tonsurans (MIC: 0.75 mg mL-1) and N. gypsea (MIC: 0.75 mg mL-1), followed by T. mentagrophytes (MIC: 6 mg mL-1). Regarding the type of activity recorded, against the fungus T. mentagrophytes it was of the fungiostatic type and for the fungi T. tonsurans and N. gypsea it was of the fungicide type. This was a pioneering study on the antifungal activity of the microalgae P. virginica, as well as the method of fractionation of its biomass. The microalgae demonstrated antifungal potential against the dermatophyte fungi evaluated, showing to be promising in the development of new herbal medicines and treatments.